Biological Phosphorus Removal During High-Rate, Low-Temperature, Anaerobic Digestion of Wastewater - Keating, Ciara; Chin, Jason P.; Hughes, Dermot; Manesiotis, Panagiotis; Cysneiros, Denise; Mahony, Therese; Smith, Cindy J.; McGrath, John W.; O’Flaherty, Vincent (Frontiers in Microbiology, 2016)
We report, for the first time, extensive biologically-mediated phosphate removal from wastewater during high-rate anaerobic digestion (AD). A hybrid sludge bed/fixed-film (packed pumice stone) reactor was employed for low-temperature (12°C) anaerobic treatment of synthetic sewage wastewater. Successful phosphate removal from the wastewater (up to 78% of influent phosphate) was observed, mediated by biofilms in the reactor. Scanning electron microscopy and energy dispersive X-ray analysis revealed the accumulation of elemental phosphorus (~2%) within the sludge bed and fixed-film biofilms. 4’, 6-diamidino-2-phenylindole (DAPI) staining indicated phosphorus accumulation was biological in nature and mediated through the formation of intracellular inorganic polyphosphate (polyP) granules within these biofilms. DAPI staining further indicated that polyP accumulation was rarely associated with free cells. Efficient and consistent chemical oxygen demand (COD) removal was recorded, throughout the 732-day trial, at applied organic loading rates between 0.4-1.5 kg COD m-3 d-1 and hydraulic retention times of 8-24 hours, while phosphate removal efficiency ranged from 28-78% on average per phase. Analysis of protein hydrolysis kinetics and the methanogenic activity profiles of the biomass revealed the development, at 12˚C, of active hydrolytic and methanogenic populations. Temporal microbial changes were monitored using Illumina Miseq analysis of bacterial and archaeal 16S rRNA gene sequences. The dominant bacterial phyla present in the biomass at the conclusion of the trial were the Proteobacteria and Firmicutes and the dominant archaeal genus was Methanosaeta. Trichococcus and Flavobacterium populations, previously associated with low temperature protein degradation, developed in the reactor biomass. The presence of previously characterised polyphosphate accumulating organisms (PAOs) such as Rhodocyclus, Chromatiales, Actinobacter and Acinetobacter was recorded at low numbers. However, it is unknown as yet if these were responsible for the luxury polyP uptake observed in this system. The possibility of efficient phosphate removal and recovery from wastewater during AD would represent a major advance in the scope for widespread application of anaerobic wastewater treatment technologies.